Driver’s reputation management system using blockchain for smart city - Siam, Md.Ammar Hossain; Mostafa, Raufar; Maisha, Maliha Jahan; Jahan, Shifath; Muhammad, Nafisa (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.